Methodology for effective use of visualizations to present information for the creation of VŠE reports - Josipović, Ivona (2024)
This thesis aims to analyze existing university reports from the UX and BA perspective and create best practice guidelines for effectively using visualizations when presenting information in reports in the university environment. The secondary is to define principles for creating and designing dashboards and applying these directions to create patterns and templates, which would help with the frontend report development in the future and, therefore, help the analytical team of VŠE to make more user-friendly and effective dashboards. Another goal is to create a template and color theme in Power BI and share it with the CDnA team of VŠE and their developers, which will help them to focus more on data analysis and save time on the layout.